KEBIJAKAN DAN STRATEGI PENGEMBANGAN E-GOVERNMENT PEMERINTAH KOTA X - wasilah murni (Jurnal Informatika, 2012)
The criteria a good government are clean government, transparent, capable to respond the changes effectively, capable to meet demand of public service, society concerns in whole country, reliable, trustworthy, affordable, and interactive. It necessary to harmonize and optimize human resource capacity, and minimize the possible obstacles of each regional to make the strategy and policy of the region in a large portion to respond technology development. So that, the regional autonomy goes along with the national goal. Analysis of harmonization including relation between government regulations about the minimum service standard, regional strategy and policy, and president instruction about development of e-government. Implementation of e-government is one of alternatives to manage regional government that can support government performance in order to adapt technology development. Keywords :Minimum service standard, SWOT, CSF, E-Government.